2018
DOI: 10.4236/ce.2018.97082
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Statistical Helplessness and Developing Statistical Resilience in Learners: An Illustrative, Collaborative, Phenomenological Study

Abstract: Many people suffer from statistics anxiety or helplessness in the UK; this is true even in the context of PhD students studying at prestigious universities. There is a risk that anxiety or helplessness results in students avoiding engagement with statistics, and consequent underachievement. Here, we illustrate the application of the construct "statistical resilience" to developing positive engagement in statistics. We used the method of a collaborative phenomenological study. The collaboration is between a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…withdrawal, depression) and externalizing problems (e.g. delinquent and aggressive behavior) Klein, Fencil-Morse and Seligman 1976;Sorrenti et al 2019); perceiving tasks that Helplessness Among University Students 4 require persistence as beyond one's reach (Abrahamson et al 1989;Ames 1990); lower achievements (Johnston-Wilder, Goodall and Almehrz 2018;Valas 2001aValas , 2001b; and burnout (Maslach and Jackson 1982).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…withdrawal, depression) and externalizing problems (e.g. delinquent and aggressive behavior) Klein, Fencil-Morse and Seligman 1976;Sorrenti et al 2019); perceiving tasks that Helplessness Among University Students 4 require persistence as beyond one's reach (Abrahamson et al 1989;Ames 1990); lower achievements (Johnston-Wilder, Goodall and Almehrz 2018;Valas 2001aValas , 2001b; and burnout (Maslach and Jackson 1982).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Work at strategic level is needed in order for them to feel they belong in the academy (Mark, 2018). The aim of this project was to provide effective teaching and learning opportunities for these adult learners, to increase their selfconfidence, enhance their wellbeing and widen their opportunities, in the knowledge that adult learners can be helped to overcome their past fears in mathematics (Johnston-Wilder et al, 2018).…”
Section: Barriers To Learning Mathematicsmentioning
confidence: 99%
“…Clarifying expectations of the need to recruit support within the learning community may encourage hesitant learners to explore possible sources of support. The ladder model (Johnston-Wilder et al, 2018) has been found to be a useful learning tool to empower learners either to ask for more rungs in the ladder or to find them for themselves.…”
Section: Establish Effective Pathways For Learning Mathematicsmentioning
confidence: 99%
“…This is intended to explore the positive contribution of the affective domain in the learning process. The scope of study of affective has begun to develop, not only examining attitudes but examining several aspects such as beliefs and emotional reactions (Ignacio et al, 2006), mathematical resilience (Hendriana et al, 2019;Johnston-Wilder et al, 2018;Johnston-Wilder et al, 2015;Kooken et al, 2013;Thornton et al, 2012), habits of mind (Costa & Kallick, 2008;Dwirahayu et al, 2017;Matsuura et al, 2013;Yellamraju et al, 2019), sociomathematical norm (Güven & Dede, 2017;Maarif et al, 2022;Sánchez & García, 2014;Yackel & Cobb, 1996;Zembat & Yasa, 2015), and so on. These affective aspects must be developed and optimized in teaching and learning activities, especially mathematics.…”
Section: Introductionmentioning
confidence: 99%